PENGEMBANGAN MEDIA PEMBELAJARAN CERITA BERGAMBAR SEJARAH LISAN BUKIT KELAM UNTUK KELAS XI SMAN 1 KAYAN HULU - Hartono; Andang Firmansyah; Astrini Eka Putri (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to develop a picture story based learning media about the oral history of Bukit Kelam as an effort to increase students’ learning interest, literacy, and understanding of local history materials. This research is motivated by the limited availability of innovative learning media and the low level of students’ interest in history, especially oral history which is rarely published. The method used in this study is the Research and Development (R&D) model with the ADDIE stages, which include needs analysis, story and visual design, development of picture-story media, implementation, and evaluation. Validation by material experts and media experts shows that the developed media product falls into the category of “very feasible.” The trial conducted with students of SMA Negeri 1 Kayan Hulu received positive responses, where students considered the media product interesting, easy to understand, and helpful in visualizing historical events. The results of this study conclude that picture stories can be used as an alternative contextual history learning media.